Rationalization in the use of mineral fertilizer in soybean production - Đukić, Vojin; Balešević Tubić, Svetlana; Đorđević, Vuk; Miladinović, Jegor; Tatić, Mladen (Economics of Agriculture, 2010)
The effect of different dosages of nitrogen fertilizers applied to the previous crop and seed inoculation with microbial fertilizer NS-Nitragin on soybean yield and consumption of mineral nitrogen from the soil was studied. The experiment was set up in the field of the Institute of Field and Vegetable Crops in four replications. Inoculation of seeds prior to sowing led to statistically highly significant yield increase in all four years of research, while the highest dosages of nitrogen contributed to a significant increase in consumption of mineral nitrogen from the soil and reduction in nitrogen fixation.